Granulomatosis with polyangiitis masquerading as pituitary adenoma with apoplexy. (3rd April 2021) - Piper, Keenan; Beldick, Stephanie R.; Karsy, Michael; Allawh, Tanya; Shirodkar, Monika; Miller, Jeffrey; Kiriakidou, Marianthi; Curtis, Mark; Evans, James J.
Abstract: Granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis, is a small- and medium-vessel autoimmune vasculitis. Rare presentations of GPA can manifest as ophthalmologic and endocrinological deficits with sellar enhancement on imaging. While GPA typically presents distinct in appearance from other sellar pathologies, such as pituitary adenoma, we report the case of a 41-year-old woman with GPA of the pituitary that was initially diagnosed as pituitary macroadenoma with apoplexy and treated with two surgical resections without improvement of clinical symptoms. Pathology analysis of the second resection specimen revealed an inflammatory process consistent with GPA. After the pathologic and clinical diagnosis of GPA was established, treatment with steroid and steroid-sparing immunosuppressants resulted in improvements both on imaging and symptomatically. We discuss important aspects of the diagnosis and treatment of this rare presentation of GPA.